Small-sided games in elite football: practical solutions to replicate the 4-min match-derived maximal intensities - Riboli, A.; Esposito, F.; Coratella, G. (The Journal of Strength and Conditioning Research, 2023)
The purpose of the study was to determine the area per player (ApP, m2·player-1) to replicate the maximal 4-min match-play period (4-minPeak) using small-sided or large-sided games (SSGs) lasting the same duration in elite football players. Twenty players (age: 26 ± 5 years) competing in European championship and international UEFA competitions were monitored during SSGs with (SSGwith) or without (SSGwithout) goalkeepers, both lasting 4-min. A total of 1,724 and 561 individual observations for SSGwith and SSGwithout across 99 and 34 different SSGs formats were undertaken. Whole (90-minavg) and 4-minPeak match demands were calculated. Relative (m·min-1) total, high-speed (HSRD), very high-speed (VHSRD), sprint, and acceleration/deceleration distance were collected. For both SSGwith and SSGwithout, ApP was small-to-very-largely correlated with TD, HSRD, VHSRD, and sprint, whereas an inverse trivial-to-small correlation with acceleration/deceleration was found. In SSGwith, the ApP to replicate 4-minPeak was larger (p < 0.001, effect size [ES]: 0.33-5.80) than that to mimic 90-minavg for total distance, HSRD, VHSRD, and sprint, whereas for acceleration/deceleration the ApP was lower (p < 0.001, ES: -3.13 to 0.48) for 4-minPeak. In SSGwithout, the ApP to replicate 4-minPeak was larger (p < 0.001, ES: 0.04-3.72) than that to mimic 90-minavg for HSRD, VHSRD, and sprint. Some positional differences (p < 0.05, ES: 0.22-1.10) in ApP were found. The ApP to replicate 4-minPeak was higher for SSGwith than SSGwithout (p < 0.001, ES: 0.67-3.58). These findings may help practitioners to recreate the 4-minPeak to manage ApP during SSGs in elite football.